Enhancing public innovation by transforming public governance - Torfing, Jacob; Triantafillou, Peter (Cambridge, United Kingdom Cambridge University Press, 2016)
Drawing on theoretical research and empirical studies, this book examines how public governance can be transformed in order to enhance public innovation
Enhancing public innovation by transforming public governance? / Jacob Torfing and Peter Triantafillou -- Collaborative governance as creative problem-solving / Chris Ansell -- The new public governance and innovation in public services : a public service-dominant approach / Stephen P. Osborne and Zoe Radnor -- Public innovations around the world / Jacob Torfing and Peter Triantafillou -- Organizational and governance aspects of diffusing public innovation / Jean Hartley -- Collaborative innovation in the public sector / Eva Sorensen and Jacob Torfing -- Public managers and professionals in collaborative innovation / Victor Bekkers and Mirko Noordegraaf -- Bringing the resources of citizens into public governance : innovation through co-production to improve public services and outcomes / Tony Bovaird and Elke Loeffler -- The role of elected politicians in collaborative policy innovation / Eva Sorensen -- The role of private actors in public sector innovation / Ole Helby Petersen, Veiko Lember, Walter Scherrer and Robert Agren -- Public innovation and organizational structure: Searching in vain for the optimal design / Mads Leth Felsager Jakobsen and Claus Thrane -- Can command and incentive systems enhance motivation and public innovation? / Lotte Bogh Andersen -- Administrative leadership for innovation / Montgomery Van Wart -- Thinking allowed : reforming indicator-based accountability to enhance innovation / Wouter Van Dooren and Tom Willems -- Organizational innovations and multiple forms of accountability in the post-new public management era / Tom Christensen and Per Lagreid -- Can public governance be changed to enhance innovation? / B. Guy Peters -- Conclusion : governing innovation and innovating governance / Jacob Torfing and Peter Triantafillou.
Includes bibliographical references and index.
Keywords: Organizational change; Organizational effectiveness; Public administration; Administrative agencies -- Reorganization; Administrative agencies -- Management